Soil erosion analysis for flood disaster assessment using GIS-based RUSLE model in Kota Belud, Sabah, Malaysia - Kamilia Sharir; Amirah Saidin; Rodeano Roslee (Research, Innovation and Creativity Administration Office, 2024)
Soil erosion is one of the significant environmental problems and main contributors to flood events, especially in the Kota Belud district of Sabah, Malaysia. A detailed assessment of soil loss prediction and its consequences was carried out in this district using the revised soil loss equation (RUSLE) model with a geographical information system (GIS). A thematic data layering method was used to analyze risk areas and identify possible high-risk erosion zones. The RUSLE model used GIS as the spatial information analysis method for calculating the amount of soil loss (tons/ac/year). Approximately 61.50% (89 ac) of the area was classified as very low risk, 2.67% (4 ac) low risk, 4.76% (7 ac) moderate risk, 3.57% (5 ac) high risk, and 27.50% (40 ac) very high risk. All the outcomes revealed that GIS integration might be used for regional spatial analysis. Total value maps can be used to plan inevitable development, such as housing, farming, and hazard and risk management.